Treatment of Hypovitaminosis D With Cholecalciferol in Dogs With Protein‐Losing Enteropathies: A Randomized, Double‐Blind, Placebo‐Controlled, Clinical Trial - Sara A. Jablonski; Sarah B. Shropshire; Victoria E. Watson; Alison C. Manchester; Harry Cridge; Elizabeth M. Lennon; M. Katherine Tolbert (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background The effects of vitamin D supplementation are unknown in dogs with protein‐losing enteropathy (PLE). Objective To evaluate the safety, efficacy, and clinical benefit of orally administered cholecalciferol in dogs with PLE and decreased serum concentrations of 25OHD. Animals Twenty‐eight dogs with PLE, decreased 25OHD, and serum ionized calcium (iCa) > 1.0 mmol/L (n = 15 treated with cholecalciferol, n = 13 treated with placebo). Methods Prospective, double‐blinded, randomized, controlled trial. Dogs randomized to receive 400 IU/kg cholecalciferol or placebo PO daily along with standard therapy for 6 weeks. Clinical and biochemical variables were measured at baseline (T0) and monitored at 2 (T1), 4 (T2), and 6 (T3) weeks postmedication initiation. Clinical and biochemical variables were also measured 6 weeks following discontinuation of study medication (T4). Variables were compared in dogs with PLE receiving cholecalciferol versus placebo at T0–T4 using Student's t test or Mann–Whitney U tests and a mixed‐effects model. Correlations between 25OHD and clinical and biochemical variables were also performed. Results Dogs with PLE treated with cholecalciferol had higher 25OHD concentrations at T2 compared to dogs treated with placebo (225 nmol/L, range 72–434 vs. 80 nmol/L, range 31–254 nmol/L; p = 0.004). Clinical and biochemical variables did not otherwise differ between dogs with PLE treated with cholecalciferol versus placebo at T0–T4. Serum albumin correlated with 25OHD at T0–T3(p < 0.005 for all comparisons). Hypervitaminosis D without ionized hypercalcemia occurred in five dogs (18%). Conclusions While PLE dogs treated with cholecalciferol had higher 25OHD concentrations at study timepoints, a clinical benefit of supplementation was not observed.